Processability study of abs impact modified PVC-U composites - effect of rice husk ash (RHA) fillers and coupling agents - Hassan, Azman (Penerbit UTM Press, 2005)

(untitled)
A processability study was conducted to investigate the fusion behavior of RHA filled ABS (Acrylonitrile Butadiene Styrene) modified PVC-U (Unplasticisied Polyvinyl Chloride) using brabender torque rheometer. The objective of this study is to investigate the effect of RHA loading and types of coupling agents on the fusion behavior of impact modified pvc-u. the study showed that in ABS impact modified PVC, RHA loading increased the fusion time. The torque decreased marginally with RHA loading. Treating the PVC compound with coupling agent increased the fusion time. the torque, However, reduced when the filled RHA PVC composites were treated with LICA 12.